The Reactive Chemisorption of Carbon Dioxide at Mg(100) Surface - Asghar Zeini Isfahani; M.W. Roberts; A.F. Carley; S. Read (Iranian Journal of Chemistry & Chemical Engineering, 1994)
X-ray photoelectron and electron energy loss spectroscopic (XPS-EELS) studies reveal that the following species are present when a mixture of CO2 and water vapour is exposed to the clean Mg(100) surface at 110K: CO3(a), C(a) CH(a), OH(a). The reactive chemisorptions of CO2 and H2O vapour coadsorbed on a Mg surface leads to the formation of CH bond. Increasing the temperature to 400 K shows the peaks in the C(1s) region of the spectrum disappears suggesting the CH containing species are not stable at 400K.